Estudo por espectroscopia Raman de efeitos de localização das excitações elementares em superredes e em ligas dopadas - Carrasco, Veronica Elsa Espinoza (Universidade Federal de São Carlos, 2005)
In the present work, the localization properties of the single-particle and collective excitations subjected to a random potential in the AlGaAsSi alloys and in the intentionally disordered GaAs/AlGaAs:Si superlattices (SL s)were investigated by magnetoresistance and Raman scattering. As it is well known, the fluctuations of the eletronic potential, which occur in doped SL s and alloys destroy the translational invariance giving rise to a spatial coherence length of the elementary excitations and, as consequence, cause the breakdown of the Raman selection rules leading to the broadening and assymetry of the Raman lines. The analysis of the shape of the spectral lines allows one to determine the coherence lengths of the elementary excitations involved in the Raman process and thus, to study their localization properties. It was shown that the Landau damping determines the localization lengths of the collective plasmon-like excitations in bulk AlGaAs alloy. Meanwhile the localization lengths of both,the single-particle and collective excitations are limited by disorder in the intentionally disordered superlattices. The localization lengths of the plasmon-like excitations obtained by Raman Spectroscopy was compared with the phase-breaking lengths measured by Magnetoresistance. We had verified that in superlattices the localization length of the individual electron was found to be considerably larger than localization length corresponding to the collective excitations. This suggests that the effect of disorder has weaker influence on the electrons than on their collective motion and that the interaction, which gives rise to the collective effects, increase the localization.
Keywords: Física da matéria condensada; Raman, Espectroscopia de; Super redes; Interação plasmon-fonon; Desordem; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA